Analytical, experimental, and numerical analysis of a microchannel cooling system for high-concentration photovoltaic cells - Ortegon, J. A.A. [UNESP]; Souza, R. R. [UNESP]; Silva, J. B.C. [UNESP]; Cardoso, E. M. [UNESP] (Springer Nature, 2019)
In this work, we present the results of an analytical, numerical, and experimental analysis on the performance of a heat sink system designed as a parallel arrangement of microchannels for cooling a high-concentration photovoltaic (HCPV) cell. The analysis considered the worst-case scenario where no electricity is generated, and the solar incidence is maximum on the northwest region of the São Paulo State in Brazil. For the experimental, analytical, and numerical analysis, the considered HCPV cell has a geometrical concentration ratio of 500×, a maximum efficiency of 40% at cell’s operating temperature of 41.0 °C, and a cell base area of 100 mm2. The numerical analysis adopts the finite volume method implemented in ANSYS Fluent v15 to solve flow and energy equations with second-order upwind schemes, and the steady-state, incompressible, and laminar flow. In the experimental apparatus, the copper microchannel heat sink consists of 33 parallel rectangular channels of 10 mm in length, 200 μm in width, and 500 μm in height for each microchannel. A cartridge heater was used to simulate the on-sun test, i.e., it simulates the total heat rate supplied to the microchannel heat sink. The microchannel heat sink is capable of keeping the operating temperature of the cell below the maximum cell’s operating temperature (41.0 °C). In addition, the pressure drops are slightly higher than the predicted models, but not exceeding 34%. Moreover, the energy spent in the pumping in the microchannel represents < 1% of the energy generated by the photovoltaic cell.
Keywords: Microchannel heat sink; Photovoltaic cell; Solar applications